2009
DOI: 10.2754/avb200978020319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Propylparaben on Vitellogenesis and Sex Ratio in Juvenile Zebrafish (Danio rerio)

Abstract: The aim of the study was to evaluate the xeno-oestrogenic potential of propylparaben in vivo using zebrafish (Danio rerio). Experimental juvenile zebrafish (20 days post hatching) were fed a feed containing 500, 1000, or 2000 mg·kg -1 of propylparaben, fish in a positive control group were given a feed treated with 20 mg·kg -1 of 17β-oestradiol, and the control fish were given the feed free of either tested substance. The exposure of fish to propylparaben did not affect vitellogenesis after 20 days exposure bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Sex hormones play an important role in sexual differentiation in teleosts, and exposure to exogenous steroids during the critical developmental period can alter phenotypic sex (Hill and Janz, 2003;Mikula et al, 2009). Andersen et al (2003) found that 15.4 ± 1.4 ng/L EE 2 had an extremely potent feminizing effect on gonadal differentiation in zebrafish when applied from 20 to 60 dph or from hatching to 60 dph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex hormones play an important role in sexual differentiation in teleosts, and exposure to exogenous steroids during the critical developmental period can alter phenotypic sex (Hill and Janz, 2003;Mikula et al, 2009). Andersen et al (2003) found that 15.4 ± 1.4 ng/L EE 2 had an extremely potent feminizing effect on gonadal differentiation in zebrafish when applied from 20 to 60 dph or from hatching to 60 dph.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish (Danio rerio) is a good model with which to test this hypothesis because this species exhibits gonadal abnormalities in response to a number of estrogen-like chemicals (Xu et al, 2008;Mikula et al, 2009). Male zebrafish pass through a phase of juvenile hermaphroditism.…”
Section: Introductionmentioning
confidence: 99%
“…For river sediments and sewage sludge, PrP was found at 0.59e4.03 ng/g d.w (Núñez et al, 2008) and 7e10 ng/g d.w. (Nieto et al, 2009), respectively. Although PrP has been acknowledged as safe for humans (Elder, 1984;Soni et al, 2005), it has been shown to induce weakly estrogen responses in human and yeast cell lines (Routledge et al, 1998;Okubo et al, 2001;Byford et al, 2002) and in fish in vivo (Pedersen et al, 2000;Inui et al, 2003;Mikula et al, 2006Mikula et al, , 2009 after activating the estrogen receptor. Using common vertebrate and invertebrate models, Dobbins et al (2009) performed the hazard assessment for seven parabens.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, salmonid fish are the most sensitive freshwater fish species to aqueous aluminium (Howells et al 1990). The aquarium fish Danio rerio, which was chosen for the toxicity tests performed during our study, is often used for the assessment of the toxic effects of chemicals (Jurčíková et al 2007;Voslářová et al 2008;Mikula et al 2009). …”
mentioning
confidence: 99%